A strain sensor with low temperature crosstalk based on re-modulation of D-shaped LPFG. (June 2021) - Jin, Xiren; Lu, Chupeng; Lin, Jingyu; Chen, Xudong; Li, Xiaoyang; Xiang, Zihang; Yang, Xinghua; Tong, Chengguo; Yan, Yunxiang; Geng, Tao; Sun, Weimin; Yuan, Libo
Highlights: A new structure based on re-modulating D-shaped long-period fiber grating (D-LPFG) is proposed and studied. It improves the strain sensitivity and has the ability to carry out strain measurement with almost no temperature crosstalk. The re-modulation of the high frequency CO2 laser is important to achieve the maximum coupling coefficient. Abstract: In this paper, a sensor with high strain sensitivity and low temperature crosstalk is proposed. The proposed sensor is configured by re-modulating the D-shaped long-period fiber grating (D-LPFG). D-LPFG is fabricated by CO2 laser polishing method. Re-modulation refers to etching on the D-LPFG with CO2 laser. A new resonant dip appears after re-modulation. The re-modulation based on CO2 laser etching method changes the distribution of refractive index, which leads to the variation of coupling coefficients. Resonant dip A and dip B with wavelengths at 1301.5 nm and 1565.7 nm are selected to measure strain and temperature. Experimental results show that the strain and temperature sensitivities of the resonant dip A are 9.37 pm/με and 57.00 pm/°C, respectively. The strain and temperature sensitivities of the resonant dip B are −1.38 pm/με and 57.14 pm/°C, respectively. Through calculation, the strain sensitivity of the proposed LPFG reaches 10.75 pm/με with only 0.14 pm/°C temperature sensitivity. The temperature crosstalk is 0.013 με/°C. Therefore, the proposed LPFG can be used as a sensor for strain measurement with extremely low temperature crosstalk.